Comparative Analysis of Competition Authority Decisions Based on Mergers and Acquisitions in the Philippines, Malaysia, and Indonesia - Asmah, Asmah (Journal of Progressive Law and Legal Studies, 2023)
In order to compare merger and acquisition decisions made by competition authorities in the Philippines, Malaysia, and Indonesia, this study will investigate each country's decisions. This study aims to pinpoint the variations in the strategies and practices used by competition authorities in the three nations and examine how they affect the preservation of healthy economic competition and the general welfare. The research involves gathering and studying merger and acquisition-related decisions made by competition authorities in the Philippines, Malaysia, and Indonesia. Differences in each nation's determination of the approval requirements, oversight procedures, and sanctions were discovered through this investigation. The findings demonstrate that there are differences between the strategies used by competition authorities in Indonesia, Malaysia, and the Philippines in relation to mergers and acquisitions. The applied threshold standards, sanctions policies, and legal interpretations vary. The results shed light on the initiatives taken by each nation to uphold fair competition and consumer protection.